2002
DOI: 10.1097/00003246-200211000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of the effects of nebulized nitroprusside versus inhaled nitric oxide on pulmonary and systemic hemodynamics during hypoxia-induced pulmonary hypertension in piglets

Abstract: Both inhaled nitric oxide and nebulized nitroprusside produced prompt, significant, selective reduction of pulmonary artery pressure and pulmonary vascular resistance in piglets with hypoxia-induced pulmonary hypertension, without apparent effects on systemic hemodynamics or pulmonary gas exchange. The equivalence of the two effects in this animal model suggests that cautious extrapolation of the use of nebulized nitroprusside as a convenient bridge to inhaled nitric oxide in selected clinical contexts for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Inhaled alternatives to NO, including sodium nitroprusside (31,32), nebulized nitroglycerine (32,33), and various NONOates (34) have shown promise but are less well understood from the standpoint of structure-function relationships. We recently showed that the nitrosalcohol gas ENO has activity similar to that of NO but is resistant to reactions with O 2 that generate potentially toxic NO x .…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled alternatives to NO, including sodium nitroprusside (31,32), nebulized nitroglycerine (32,33), and various NONOates (34) have shown promise but are less well understood from the standpoint of structure-function relationships. We recently showed that the nitrosalcohol gas ENO has activity similar to that of NO but is resistant to reactions with O 2 that generate potentially toxic NO x .…”
Section: Discussionmentioning
confidence: 99%
“…When administered through a nebulizer connected to the inspiratory limb of the breathing circuit, SNP has been shown to be a selective pulmonary vasodilator. [ 22 23 ] In a porcine model of PH,[ 24 ] nebulized SNP (total dose of 25 mg) caused a rapid reduction in PAP that was equivalent to iNO at 20 ppm, without decreasing MAP. In a sheep model of PH,[ 25 ] low-dose inhaled SNP (concentration ≤0.02 M) decreased PAP by 42% and systemic vascular resistance (SVR) by 5%.…”
Section: Inhaled Nitric Oxide Donorsmentioning
confidence: 99%
“…2 There are several differences between the two studies. Based on our preliminary animal studies, 3,4 we were able to use a much higher dose of sodium nitroprusside. Second, Palhares' study group was comprised of 50% premature infants (gestational age range, 28-36 weeks), whereas our study was limited to term infants.…”
Section: Replymentioning
confidence: 99%